Mathematical Connection Abilities and Self-Esteem of Students on Model-Eliciting Activities Learning with a Realistic Approach - Dinni, Husna Nur; Isnarto, Isnarto (Unnes Journal of Mathematics Education Research, 2018)
This study has purpose to (1) find out the quality of Model-Eliciting Activities learning with a realistic approach, (2) describe the ability of mathematical connection based on student’s self-esteem. This research applied mixed method research type with sequential explanatory design, and sample in this study was students of grade VIII.1 and VIII.2 of SMP Negeri B. Srikaton in Musi Rawas District, South Sumatra. Data was done by observation, test, self-esteem scale, and interview. The results of the study showed that the quality of Model-Eliciting Activities learning with a realistic approach included in the good category, and students with high self-esteem had a very good mathematical connection abilities, then students with medium category of self-esteem had a good mathematical connection abilities, and one of subject with a low self-esteem has a poor mathematical connection abilities but there is one subject with a low self-esteem has a fairly good mathematical connection abilities.